2011
DOI: 10.1159/000330202
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Fetal Circulation Associated with Congenital Heart Disease and Their Effects on Fetal Growth

Abstract: Objective: Our aim was to investigate the association between fetal growth and cerebrovascular resistance in fetuses with congenital heart disease (CHD). Methods: Fetal echocardiography was performed to measure the biparietal diameter, abdominal circumference, femur length, estimated fetal body weight, middle cerebral artery (MCA) resistance index (RI) and umbilical artery (UA) RI in 44 fetuses with CHD and 140 normal fetuses at a gestational age of 28–34 weeks. Results: Fetuses with CHD exhibited significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…226,245,246 The CVP score may be useful in the baseline and serial evaluations for fetuses at risk for or with myocardial dysfunction. Finally, abnormalities of myocardial structure and function may affect the fetal circulation, including placental blood flow and fetal growth, 247 and conversely, placental pathology may contribute to fetal hemodynamic compromise through fetal hypoxia. 226,227 The assessment of umbilical artery pulsatility may be useful in these conditions.…”
Section: Cardiac Function Assessmentmentioning
confidence: 99%
“…226,245,246 The CVP score may be useful in the baseline and serial evaluations for fetuses at risk for or with myocardial dysfunction. Finally, abnormalities of myocardial structure and function may affect the fetal circulation, including placental blood flow and fetal growth, 247 and conversely, placental pathology may contribute to fetal hemodynamic compromise through fetal hypoxia. 226,227 The assessment of umbilical artery pulsatility may be useful in these conditions.…”
Section: Cardiac Function Assessmentmentioning
confidence: 99%
“…Eight studies included larger groups of mixed CHD, and five only included HLHS . Eight studies calculated z ‐scores or percentiles to correct for the effect of gestational age, using various normal reference populations (Table b) . One study reported absolute values at 34 weeks of gestation .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ( n = 14) calculated z ‐scores or percentiles to correct for the effect of the gestational age, using various normal reference populations (Table b) . Seven studies reported absolute values at a specific gestational age . Three articles were excluded from the meta‐analysis because the pulsatility indices were not available .…”
Section: Resultsmentioning
confidence: 99%
“…In adults, elevated MCA PSV has been reported in association with subarachnoid hemorrhage, cerebral edema leading to extravascular compression and vasospasm . Otherwise, it can be speculated that changes in MCA could be related with changes in cardiac function, as demonstrated in fetuses with congenital heart defects . All these alternative explanations require further consideration.…”
Section: Discussionmentioning
confidence: 97%